2016
DOI: 10.3758/s13414-016-1167-7
|View full text |Cite
|
Sign up to set email alerts
|

Does perceptual or motor experience influence the perception of global and joint-specific kinematic changes in complex movement patterns?

Abstract: The perception and identification of technical errors during skill execution is a critical component in coaching, because it provides the foundation for skill analysis, instruction, and feedback provision. In this study, we examined the influences of perceptual and motor experience on the perception of kinematic change in a technical evaluation task that is common in coaching. A total of 21 expert coaches, stratified by playing (Bmotor^) expertise, as well as ten novice coaches and ten current players, observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Further investigation into the specific verbal comments made by participants and the biomechanics of the athletes may shed more light on this video observation skill that is a prevalent part of modern coaching. The error detection ability or visual sensitivity to changes in body positions of coaches and biomechanists are two potential directions that have already given insights into expert tennis coaches perceptual abilities and are potentially worth exploring in sprint coaches and biomechanists (Giblin et al, 2016). Another limitation of this research is the use of videos obtained in a controlled environment and displayed at fixed speeds, potentially collecting the visual and verbal data "live" in actual coaching sessions or during competition would reveal different insights into behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Further investigation into the specific verbal comments made by participants and the biomechanics of the athletes may shed more light on this video observation skill that is a prevalent part of modern coaching. The error detection ability or visual sensitivity to changes in body positions of coaches and biomechanists are two potential directions that have already given insights into expert tennis coaches perceptual abilities and are potentially worth exploring in sprint coaches and biomechanists (Giblin et al, 2016). Another limitation of this research is the use of videos obtained in a controlled environment and displayed at fixed speeds, potentially collecting the visual and verbal data "live" in actual coaching sessions or during competition would reveal different insights into behavior.…”
Section: Discussionmentioning
confidence: 99%
“…The video analysis method was previously used by Graham et al (1993) in a study of physical education teachers' ability to observe and interpret instructional events at different stages of teaching expertise. This technique has also been previously used in research on coaches' perceptions (Giblin et al, 2016). This technique yielded information regarding "cue acquisition, cue interpretation, and diagnostic decisions" (Pinheiro & Simon, 1992, p. 289).…”
Section: Data Collectionmentioning
confidence: 99%
“…A study similar to the current investigation examined the influences of coaching and playing experience on perceptions of kinematic changes in a tennis serve (Giblin, Farrow, Reid, Ball, & Abernethy, 2016). The participants were 21 coaches averaging 15 years coaching experience and holding or pursuing their country's highest coaching certification, 10 novice coaches (average 5 years experience) and 10 current tennis players.…”
mentioning
confidence: 96%
“…However, research on body angle discrimination and related visual biases has suggested that there is a critical JND in the magnitude of body angles that can be perceived. body angles above a conservative perceptual threshold of 15° per body segment seem to be applicable for complex biological motion kinematics [20][21][22][23]. For example, Giblin et al [21] investigated whether expert coaches, novice coaches, and tennis players differred in their ability to detect kinematic changes in tennis serves.…”
Section: Introductionmentioning
confidence: 99%
“…body angles above a conservative perceptual threshold of 15° per body segment seem to be applicable for complex biological motion kinematics [20][21][22][23]. For example, Giblin et al [21] investigated whether expert coaches, novice coaches, and tennis players differred in their ability to detect kinematic changes in tennis serves. the angle of maximum knee flexion, the angle of maximum trunk rotation, and the height of ball toss were manipulated by a tennis player executing the tennis serve.…”
Section: Introductionmentioning
confidence: 99%